Mega retail businesses and shopping behaviour among consumers in Alimosho local government area of lagos state (UNIZIK Journal of Marketing, 2024)
The study focused on mega retail businesses and shopping behaviour among consumers in Alimosho Local Government area in Nigeria as its main objective.  The population of the study consisted of 1,953 retail customers as provided for by the mega retail owners through their customers records. 390 customers were randomly selected using stratified random sampling. The research instrument used is a validated questionnaire with Cronbach alpha 0.7. Data gathered were analyzed using multiple regression. The study found out that variety of products, price tag, meeting specific needs and promotional offers by mega retail businesses collectively determined change in shopping behaviour of consumers in Alimosho local government area of Lagos state. Also, availability of variety of products, was the most fundamental predictor that attracts consumers to most mega retail business outlets followed by price tag, all the other predictors namely, needs specifications and promotional offers are good
Keywords: Price tags; shopping behaviour; variety of products; retail businesses